2021
DOI: 10.2196/29875
|View full text |Cite
|
Sign up to set email alerts
|

Recent Academic Research on Clinically Relevant Digital Measures: Systematic Review

Abstract: Background Digital clinical measures collected via various digital sensing technologies such as smartphones, smartwatches, wearables, ingestibles, and implantables are increasingly used by individuals and clinicians to capture health outcomes or behavioral and physiological characteristics of individuals. Although academia is taking an active role in evaluating digital sensing products, academic contributions to advancing the safe, effective, ethical, and equitable use of digital clinical measures … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Ensuring they are developed and deployed within the right environment, with diverse teams and appropriate safeguards is critical if value is to be realized [90][91][92][93]. Research into ethical and privacy matters related to digital health is expanding but still remains underexplored [94]. Engagement has also been a challenge across all digital measures in mental health to date [95], but when technology is created with patient feedback [96] and data are used to advance patient care, engagement can actually be quite high [97].…”
Section: "From Efficacy To Effectiveness" Use Casesmentioning
confidence: 99%
“…Ensuring they are developed and deployed within the right environment, with diverse teams and appropriate safeguards is critical if value is to be realized [90][91][92][93]. Research into ethical and privacy matters related to digital health is expanding but still remains underexplored [94]. Engagement has also been a challenge across all digital measures in mental health to date [95], but when technology is created with patient feedback [96] and data are used to advance patient care, engagement can actually be quite high [97].…”
Section: "From Efficacy To Effectiveness" Use Casesmentioning
confidence: 99%
“…There are several specific technical hurdles that get in the way of effective data integration, including the plethora of formats [ 29 , 30 ] and the corresponding lack of consensus around common metadata standards [ 14 , 26 ], although progress is being made [ 31 ]. Perhaps more worrisome is the fact that permissioning and consent often exclude integration and exploration [ 32 ], and massive gaps in digital health research remain regarding data rights and governance [ 33 , 34 ].…”
Section: What Are the Key Issues?mentioning
confidence: 99%
“…Moreover, understanding the legal and ethical consequences of sharing and integrating sensor data is at a nascent stage [ 45 ]. Recent work has shown that “the three most underrepresented areas of research into digital clinical measures were ethics, security, and data rights and governance” [ 33 ].…”
Section: What Are the Key Issues?mentioning
confidence: 99%
“…Ultimately, the same technology could be used both in and outside the hospital, diminishing the difference between in-patient and out-patient care even further. Clinical research should keep up with these developments, and place the focus of research beyond simply assessing the validity of sensor measurements [66]. This includes the aim to:…”
Section: Future Perspectives and Opportunities For Further Researchmentioning
confidence: 99%
“…Since big data storage will be needed to achieve this aim, health care institutions will also have to carefully consider 9. How to organise storage, standards, security, ethics, data rights, and governance [66].…”
Section: Future Perspectives and Opportunities For Further Researchmentioning
confidence: 99%